Production and secretion of functional SARS-CoV-2 spike protein in Chlamydomonas reinhardtii - Kiefer, Anna Maria; Niemeyer, Justus; Probst, Anna; Erkel, Gerhard; Schroda, Michael (Frontiers in Plant Science, 2022)
The spike protein is the major protein on the surface of coronaviruses. It is therefore the prominent target of neutralizing antibodies and consequently the antigen of all currently admitted vaccines against SARS-CoV-2. Since it is a 1273-amino acids glycoprotein with 22 N-linked glycans, the production of functional, full-length spike protein was limited to higher eukaryotes. Here we report the production of full-length SARS-CoV-2 spike protein – lacking the C-terminal membrane anchor – as a secreted protein in the prefusion-stabilized conformation in the unicellular green alga Chlamydomonas reinhardtii. We show that the spike protein is efficiently cleaved at the furin cleavage site during synthesis in the alga and that cleavage is abolished upon mutation of the multi-basic cleavage site. We could enrich the spike protein from culture medium by ammonium sulfate precipitation and demonstrate its functionality based on its interaction with recombinant ACE2 and ACE2 expressed on human 293T cells. Chlamydomonas reinhardtii is a GRAS organism that can be cultivated at low cost in simple media at a large scale, making it an attractive production platform for recombinant spike protein and other biopharmaceuticals in low-income countries.